OUT-IN PROTOCOVID: UNDERSTANDING AND IMPLEMENTATION OF COVID-19 HEALTH PROTOCOL IN COMMUNITY - Sabtanti Harimurti; Pinasti Utami; Nurul Maziyyah; Puguh Novi Arsito (Jurnal Pengabdian Pada Masyarakat MEMBANGUN NEGERI, 2022)
The Covid-19 pandemic has been on its anniversary and it is not yet seen when it will end. Vaccination and health promotion have been carried out by the government. However, it seems that it has not been able to reduce or even stop the pandemic. An alternative way that is considered effective to prevent the transmission of the Covid-19 virus is to comply with health protocols. One of the health protocols that are considered very helpful in preventing the transmission of Covid-19 is the readiness of preparing personal equipment (Starter Kits), especially when outside of the house. In this paper, will be reported an analysis of community readiness regarding their readiness to prepare a Starter kit for foreign students at Khon Kaen Universiti (KKU) and also ordinary people in the Karangtalun, Wukirsari, Imogiri, Yogyakarta area. The evaluation was carried out by asking several questions about whether when leaving the house they spare a mask, hand sanitizer, own eating utensils, drinking bottles, and also their worship tools. Questions are given online or offline using a G-form or question sheet when socializing the Covid-19 pandemic. The results of the evaluation on the readiness of bringing the starter kits from all participants, totaling 44 people, 53.57% of people answered "yes", 25 % of people answered "sometimes", and 21.43% of people answered "no". Based on these results, it can be concluded that most people are aware of the importance of preparing a starter kit while outside the house to prevent the transmission of the Covid 19 virus.